Targeted Inter-Homologs Recombination in Arabidopsis Euchromatin and Heterochromatin - Shdema Filler-Hayut (MDPI AG, 2021)
Homologous recombination (HR) typically occurs during meiosis between homologs, at a few unplanned locations along the chromosomes. In this study, we tested whether targeted recombination between homologous chromosomes can be achieved via Clustered Regulatory Interspaced Short Palindromic Repeat associated protein Cas9 (CRISPR-Cas9)-induced DNA double-strand break (DSB) repair in Arabidopsis thaliana. Our experimental system includes targets for DSB induction in euchromatic and heterochromatic genomic regions of hybrid F1 plants, in one or both parental chromosomes, using phenotypic and molecular markers to measure Non-Homologous End Joining and HR repair. We present a series of evidence showing that targeted DSBs can be repaired via HR using a homologous chromosome as the template in various chromatin contexts including in pericentric regions. Targeted crossover was rare, but gene conversion events were the most frequent outcome of HR and were found in both “hot and cold” regions. The length of the conversion tracts was variable, ranging from 5 to 7505 bp. In addition, a typical feature of these tracks was that they often were interrupted. Our findings pave the way for the use of targeted gene-conversion for precise breeding.